Determinação de contaminantes emergentes em água utilizando microextração adsortiva em barra (BAμE) e UHPLC-MS/MS - Souza, Maiara Priscilla de (2016)
The emerging pollutants are substances that enter continuously in the environment and are being more recognize due to the advancement of instrumental and sample preparation techniques. These contaminants include several chemical classes, such as pharmaceuticals, hormones, personal care products, flame retardants and others. Water is one of the most susceptible matrix since the sewage discharge is one of the main routes of environmental pollution. Bar adsorptive microextration (BAμE) has shown great analytical capacity for the analysis of organic compounds in residual level and has become a well-established analytical tool in sample preparation. In this work, a simple and low cost method was validated for the analysis of 13 emerging contaminants in water using BAμE with polymeric sorbent followed by ultra high performance liquid chromatography with tandem mass spectrometry (UHPLC-MS/MS). The preparation, stability tests and development of BAμE devices are also discussed. Eleven different coating phases were evaluated. In order to select the best combination of experimental conditions for extraction and back extraction, central composite design (CCD) with four variables was applied. Validation results were satisfactory, since the method presented recoveries between 74% and 118% with relative standard deviations (RSD) < 19%. The analytical performance presented detection and quantification limits of 0.012 to 0.6 and 0.04 to 2 μg L-1, respectively. The proposed method combines a simple and effective sample preparation for the determination of emerging contaminants in water using a microextraction technique (BAμE) followed by UHPLC-MS/MS analysis. The method applicability was evaluated using real samples of surface, drinking and tap water and 6 positive samples were found indicating the presence of bisphenol A (0.08-0.665 μg L-1) and paracetamol (0.104-4.2 μg L-1).